Variability of levee failure mechanisms subject to heavy rainfalls, case studies in Taiwan. Issue 4 (1st October 2016) - Huang, Wen-Chao; Yu, Hong-Wen
ABSTRACT: In this study, the failure mechanisms for Chiuliao 1st Levee and Gueishan Levee in Taiwan were re-examined comprehensively considering the uncertainty of different parameters. Results have shown that for Chiuliao 1st Levee, the slope sliding failure has a higher coefficient of variation (COV). For Gueishan Levee, retaining wall sliding and overturning failure have higher values of COV instead. It can also be found that the scouring depths affect the stability of the levee significantly, therefore, a protecting system for the backfill material may be necessary to increase the stability of the levee effectively.